PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN AFEKTIF DENGAN MEDIASI PERASAAN BANGGA MENJADI PENGIKUT - Suryadinatha, Putu Gede; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen, 2017)
The purpose of this study is to determine the effect of transformational leadership toward affective commitment mediated by pride in being a follower for the contract nurses in Mangusada Badung District General Hospital. The samples taken were 151 respondents, by using a probability sampling method, particularly proportionate random sampling. The data collection was done by distributing questionnaires using 5-point Likert scale to measure 15 statement items. The analysis technique used was Path Analysis. The result shows that transformational leadership has positive and significant effects on affective commitment, transformational leadership has positive and significant effects on pride in being a follower, pride in being a follower has positive and significant effects on affective commitment, and the research also proves that transformational leadership has effects on affective commitment mediated by pride in being a follower.
Keywords: transformational leadership, pride in being a follower, affective commitment